Ischemic Stroke Temporally Associated With New-Onset Atrial Fibrillation: A Population-Based Registry-Linkage Study - Putaala Jukka; Teppo Konsta; Halminen Olli; Haukka Jari; Tiili Paula; Jaakkola Jussi; Karlsson Elin; Linna Miika; Mustonen Pirjo; Kinnunen Janne; Kiviniemi Tuomas; Aro Aapo; et al. (United States, 2025)
BACKGROUND:
Limited data exist on the temporal relationship between new-onset atrial fibrillation (AF) and ischemic stroke and its impact on patients’ clinical characteristics and mortality.
METHODS:
A population-based registry-linkage database includes all patients with new-onset AF in Finland from 2007 to 2018. Ischemic stroke temporally associated with AF (ISTAF) was defined as an ischemic stroke occurring within ±30 days from the first AF diagnosis. Clinical factors associated with ISTAF were studied with logistic regression and 90-day survival with Cox proportional hazards analysis.
RESULTS:
Among 229 565 patients with new-onset AF (mean age, 72.7 years; 50% female), 204 774 (89.2%) experienced no ischemic stroke, 12 209 (5.3%) had past ischemic stroke >30 days before AF, and 12 582 (5.8%) had ISTAF. The annual proportion of ISTAF among patients with AF decreased from 6.0% to 4.8% from 2007 to 2018. Factors associated positively with ISTAF were higher age, lower education level, and alcohol use disorder, whereas vascular disease, heart failure, chronic kidney disease cancer, and psychiatric disorders were less probable with ISTAF. Compared with patients without ischemic stroke and those with past ischemic stroke, ISTAF was associated with ≈3-fold and 1.5-fold risks of death (adjusted hazard ratios, 2.90 [95% CI, 2.76–3.04] and 1.47 [95% CI, 1.39–1.57], respectively). The 90-day survival probability of patients with ISTAF increased from 0.79 (95% CI, 0.76–0.81) in 2007 to 0.89 (95% CI, 0.87–0.91) in 2018.
CONCLUSIONS:
ISTAF depicts the prominent temporal clustering of ischemic strokes surrounding AF diagnosis. Despite having fewer comorbidities, patients with ISTAF had worse, albeit improving, survival than patients with a history of or no ischemic stroke.